Paroxysmal Kinesigenic Dyskinesia Caused by 16p11.2 Microdeletion. (17th November 2014) - Termsarasab, Pichet; Yang, Amy C.; Reiner, Jennifer; Mei, Hui; Scott, Stuart A.; Frucht, Steven J.
Background: Four cases of paroxysmal kinesigenic dyskinesia (PKD) have been reported in individuals with proximal 16p11.2 microdeletions that include PRRT2 . Case Report: We describe a fifth patient with PKD, features of Asperger's syndrome, and mild language delays. Sanger sequencing of the PRRT2 gene did not identify any mutations implicated in PKD. However, microarray-based comparative genomic hybridization (aCGH) detected a 533.9-kb deletion on chromosome 16, encompassing over 20 genes and transcripts. Discussion: This case underscores the importance of aCGH testing for individuals with PKD who do not have PRRT2 mutations, particularly when developmental delays, speech problems, intellectual disability, and/or autism spectrum disorder are present.